Nested Autobiography: Life Writing Within Larger Works. Issue 2 (2nd April 2020) - Templeman, David
ABSTRACT: It is well known that one of the great literary genres in Tibet was that of autobiography. This paper commences with some observations of what might be referred to as 'encapsulated' or 'nested' autobiographies which are found within larger works. These nested autobiographies often claim that they are the 'true' account of the life and sometimes tend to dismiss the longer versions. The author of the paper contends that this genre of writing has not yet been studied in any depth and has in fact been barely noticed and asks the extent to which this was a genre which might have existed much earlier in Tibetan literature. The paper then goes on to examine Tāranātha's 15-part small autobiography which occurs at the mid-point of his large autobiography and shows how in certain of the sections the author alludes to examples drawn from his own life. An appendix offers a full preliminary translation of the 15-part 'nested' autobiography.